2013
DOI: 10.1080/19419899.2013.774161
|View full text |Cite
|
Sign up to set email alerts
|

Who reports absence of sexual attraction in Britain? Evidence from national probability surveys

Abstract: There is little evidence about the prevalence of absence of sexual attraction, or the characteristics of people reporting this, often labelled asexuals. We examine this using data from two probability surveys of the British general population, conducted in 1990-1991 and 2000-2001. Interviewers administered face-to-face and self-completion questionnaires to people aged 16-44 years (N = 13,765 in 1990-1991; N = 12,110 in 2000-2001). The proportion that had never experienced sexual attraction was 0.4% (95% CI: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 21 publications
(63 reference statements)
2
36
0
Order By: Relevance
“…Studies have reported that a sizeable minority of the population lacks sexual attraction toward others. The prevalence of asexuality has been placed between 0.4% (Aicken, Mercer & Cassell, 2013) and 1% (Bogaert, 2004) of the population, with one study finding as high as 1.5% of men and 3.3% of women, though this only addressed sexual attraction experienced in the preceding 12 months (Hšglund, Jern, Sandnabba & Santtila, 2014). …”
Section: Implicit and Explicit Attitudes Toward Sex And Romance In Asmentioning
confidence: 99%
“…Studies have reported that a sizeable minority of the population lacks sexual attraction toward others. The prevalence of asexuality has been placed between 0.4% (Aicken, Mercer & Cassell, 2013) and 1% (Bogaert, 2004) of the population, with one study finding as high as 1.5% of men and 3.3% of women, though this only addressed sexual attraction experienced in the preceding 12 months (Hšglund, Jern, Sandnabba & Santtila, 2014). …”
Section: Implicit and Explicit Attitudes Toward Sex And Romance In Asmentioning
confidence: 99%
“…Also, quantitative approaches that allow for parsimonious, single-item measurement are more feasible in large sample, random surveys which normally do not have the room necessary to capture the full variety of asexual manifestations, and for which smaller categories associated with lack of sexual attraction can’t be meaningfully measured nor relationships tested due to sample size and power constraints when using a random, non-convenience sample (Aicken, Mercer, & Cassell, 2013). However, the alternative, convenience sampling from asexuality organizations, sacrifices representativeness.…”
Section: Methodsmentioning
confidence: 99%
“…According to Bogaert (), 1.05% of the British population is asexual. More recent prevalence estimates based on a definition of a lifelong absence of sexual attraction among those aged 16–44 suggest asexuality is experienced by 0.3% of men, and 0.5% of women in the United Kingdom (UK; Aicken, Mercer, & Cassell, ). Whilst the work of Bogaert () and Aicken et al.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the work of Bogaert () and Aicken et al. () rests on problematic definitions of asexuality based on absence of or lack of sexual attraction (Carrigan, ), there is no other UK data regarding prevalence. What is also relevant here is that, as Carrigan () points out defining asexuals as experiencing no sexual attraction, rather than low, may exclude a sizable number of those who embrace an asexual identity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation